2015
DOI: 10.3897/zookeys.540.6013
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric divergence in populations of Anastrepha obliqua (Diptera, Tephritidae) from Colombia and some Neotropical locations

Abstract: The West Indian fruit fly, Anastrepha obliqua, is one of seven species of quarantine importance of its genus and is one of the most economically important fruit fly pests in Colombia. The taxonomic status of this species is a key issue for further implementation of any pest management program. Several molecular studies have shown enough variability within Anastrepha obliqua to suggest its taxonomic status could be revised; however, there are no morphological studies supporting this hypothesis. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In order to establish or dispel the existence of an A. obliqua cryptic species complex, examining reproductive isolation among South American populations, in particular from Peru, could yield conclusive results. Peruvian A. obliqua appears to be consistently different from samples of other North, Central and South American regions both at the morphological (Castañeda, Selivon, Hernández‐Ortiz, Soto, & Canal, ) and the molecular levels (Ruiz‐Arce et al., ; Scally et al., ). An analysis of reproductive compatibility of the Peruvian type against the Western Mexican and/or Eastern Brazilian types should greatly contribute to clarify the integrity of A. obliqua as a widespread Neotropical species or as a complex potentially composed of two or three cryptic species.…”
Section: Discussionmentioning
confidence: 94%
“…In order to establish or dispel the existence of an A. obliqua cryptic species complex, examining reproductive isolation among South American populations, in particular from Peru, could yield conclusive results. Peruvian A. obliqua appears to be consistently different from samples of other North, Central and South American regions both at the morphological (Castañeda, Selivon, Hernández‐Ortiz, Soto, & Canal, ) and the molecular levels (Ruiz‐Arce et al., ; Scally et al., ). An analysis of reproductive compatibility of the Peruvian type against the Western Mexican and/or Eastern Brazilian types should greatly contribute to clarify the integrity of A. obliqua as a widespread Neotropical species or as a complex potentially composed of two or three cryptic species.…”
Section: Discussionmentioning
confidence: 94%
“…The technique of geometric morphometrics applied to forewings venation indicate two distinct populations belonging two Neotropical biomes. Aytekin et al (2007) [33] studying the genus Bombus (Hymenoptera: Apidae), [34] considering the genus Eubazus (Hymenoptera: Braconidae), Francisco et al (2008) [35] in analysis of two populations of Plebeia remota (Holmberg) and Castañeda et al (2015) [36] with populations of the Anastrepha oblique (Macquart) (Diptera: Tephritidae), distinguish cryptic populations with the same technique.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the existing variabilities between populations of A. obliqua and the presumed existence of a group of cryptic species (Ruíz-Arce et al, 2012;Smith-Caldas et al, 2001), the study of Brazilian populations is extremely relevant to pest management. Castañeda et al (2015) showed significant morphological differentiation between South American populations of A. obliqua, including comparisons between Brazilian populations, demonstrating the importance of studies with different strains of A. obliqua in different regions. To date, there are no studies of radiosterilization of A. obliqua Brazilian strains.…”
Section: Introductionmentioning
confidence: 91%